2012
DOI: 10.3168/jds.2012-5507
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Genetics and modeling of milk coagulation properties

Abstract: Milk coagulation properties (MCP) are conventionally measured using computerized renneting meters, mechanical or optical devices that record curd firmness over time (CF(t)). The traditional MCP are rennet coagulation time (RCT, min), curd firmness (a(30), mm), and curd-firming time (k(20), min). The milk of different ruminant species varies in terms of CF(t) pattern. Milk from Holstein-Friesian and some Scandinavian cattle breeds yields higher proportions of noncoagulating samples, samples with longer RCT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
206
9
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(249 citation statements)
references
References 111 publications
28
206
9
6
Order By: Relevance
“…This finding is similar to that from a previous report on the Brown Swiss (Chessa et al, 2013). At present, it is not possible to establish whether the less favorable effect of the CSN2 rs43703011 A variant on RCT is due to the presence of the A 1 or B alleles, and the positive effect of the CSN2 B allele reported by Bittante et al (2012) remains controversial. Moreover, the CSN2*A 2 variant is usually found in a haplotype with the CSN3*B variant (frequency, 0.56 to 0.67; Chessa et al, 2013), suggesting that the positive effect of the CSN2 rs43703011 C allele could be confused with that of the CSN3*B variant.…”
Section: Association Analysis With Traditional Mcpssupporting
confidence: 75%
See 2 more Smart Citations
“…This finding is similar to that from a previous report on the Brown Swiss (Chessa et al, 2013). At present, it is not possible to establish whether the less favorable effect of the CSN2 rs43703011 A variant on RCT is due to the presence of the A 1 or B alleles, and the positive effect of the CSN2 B allele reported by Bittante et al (2012) remains controversial. Moreover, the CSN2*A 2 variant is usually found in a haplotype with the CSN3*B variant (frequency, 0.56 to 0.67; Chessa et al, 2013), suggesting that the positive effect of the CSN2 rs43703011 C allele could be confused with that of the CSN3*B variant.…”
Section: Association Analysis With Traditional Mcpssupporting
confidence: 75%
“…The instrument recorded the width (in mm) of the oscillatory graph every 15 s during testing and directly provided the traditional MCP traits: RCT (min), defined as the time from enzyme addition to milk gelation; k 20 (min), defined as the time from gelation to that at which the width of the graph reached 20 mm; and the widths of the graph at 30 min (a 30 , mm), from rennet addition (measuring the extent of CF). Figure 1 Modeling prolonged observations of curd firmness (CF) at t time (CF t ), model parameters: RCT = rennet coagulation time; k 20 = curd-firming time of samples reaching 20 mm of firmness within 45 min from enzyme addition; a 30 = curd firmness at 30 min after enzyme addition; CF P = potential asymptotical CF in absence of syneresis; k CF = curd firming instant rate constant; k SR = syneresis instant rate constant and representation of maximum CF traits MCF: CF max = maximum CF t value; t max = time at CF max ; modified from Bittante et al (2012).…”
Section: Field Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The physiochemical characteristics of milk and their inter-relationships are a valuable tool to evaluate the productive performance of dairy cattle, to provide information about the physiological state of the lactation, and to diagnose metabolic disorders and their possible impacts on the industrial processing and the final quality of milk products (Rowbotham and Ruegg, 2016). In the tanks of the trucks arriving at the dairy industry, samples are collected for laboratory tests, which must be taken after agitation for five to ten minutes by means of an agitator of the total volume of the tank (Di Domenico, 2009;Ponce, 2009;Bittante et al, 2012;Tonini, 2014) The fat globules are suspended in water and have a lower density than it. This causes the formation of a fat layer on top of the rest of the milk, which must be constantly stirred to prevent the formation of a too thick layer of fat at the top.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted research on NC milk can help geneticists develop breeding programs to modify milk composition and technological properties of milk and thus reduce the prevalence of NC milk. Bittante et al (2012) suggested that effects of herd have little influence on milk coagulation properties (MCP) including NC milk, although several factors can influence the composition of bovine milk (e.g., breed, a cow's diet, age of a cow, and the stage of lactation; Chilliard et al, 2001). In addition, MCP seem be influenced by many factors, such as SCC (e.g., Ikonen et al, 2004;Cassandro et al, 2008), titratable acidity (e.g., Penasa et al, 2010), casein composition (Okigbo et al, 1985b), pH (Nájera et al, 2003), stage of lactation (Okigbo et al, 1985a;Ostersen et al,1997), and breed (e.g., Auldist et al, 2004;De Marchi et al, 2007, Bittante et al, 2012, among many other factors.…”
Section: Introductionmentioning
confidence: 99%